Terrorism and Misperceptions: Evidence from Europe - K. Peren Arin; Umair Khalil; Deni Mazrekaj; Marcel Thum (Center for Economic Studies and ifo Institute (CESifo), 2023)
How does exposure to Islamist terrorism change perceptions of the share of Muslims and immigrants? We conduct a large-scale survey that measures misperceptions towards minority groups in four European countries. Our results show that terror attacks in the past increased misperceptions of the share of Muslims and immigrants. We also contend that this increase in misperceptions is particularly large and significant for lower-educated respondents and people from regions with a low share of the foreign population. Given that misperceptions are higher on average in regions with a large share of foreigners, terror attacks make misperceptions across different groups converge.
Keywords: D70; H11; H12; H41; I18; 330; terror attacks; misconceptions; public opinion; cognitive biases; prejudice; attitude formation